2009
DOI: 10.1093/humupd/dmp027
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age and reproduction

Abstract: background: Due to various sociological factors, couples in developed countries are increasingly delaying childbearing. Besides ethical, economical and sociological issues, this trend presents us with several complex problems in reproduction. Although it is well-known that maternal age has a negative effect on fertility and increases the risk of adverse outcome during pregnancy and in offspring, the paternal influence on these outcomes is less well researched and not well-known.methods: We performed a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
222
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(229 citation statements)
references
References 210 publications
(206 reference statements)
3
222
2
2
Order By: Relevance
“…The contribution of advancing female age to pregnancy outcomes is well documented, yet knowledge on effects of male age is much less [1,2]. Studies have shown that semen parameters, such as volume [3], total sperm count [4], sperm DNA integrity [3,5] and so on, would diminish with the increase of male age, which may undermine male fecundity.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of advancing female age to pregnancy outcomes is well documented, yet knowledge on effects of male age is much less [1,2]. Studies have shown that semen parameters, such as volume [3], total sperm count [4], sperm DNA integrity [3,5] and so on, would diminish with the increase of male age, which may undermine male fecundity.…”
Section: Introductionmentioning
confidence: 99%
“…35 Apart from the impact of age on the 'decline' question, it is an important issue in view of peoples' desire to start their families when older. It also resonates with the idea that free radical damage to sperm DNA increases with advancing age, leading to a related increase in the risk of genetic damage, as well as to decreased fertility (see Sartorius et al 25 and Desai et al 36 ). Here again there are huge gaps in our knowledge; the source of free radicals in the testis and epididymis is unknown, as are the defence mechanisms and why they can be overwhelmed: this will be difficult to sort out, as even the source of reactive oxygen species in sperm suspensions remains unresolved.…”
Section: Biological Factors That Could Cause Biasmentioning
confidence: 76%
“…Similar conclusions were reached by Dunson et al, 24 on the basis of 782 couples using natural family planning methods. Some of the decrease in fertility can be attributed to reduced libido and hence coital frequency, perhaps associated with erectile dysfunction (see Sartorius et al 25 and Harris et al 26 ). There is conflicting evidence about the effect of advancing age on semen quality.…”
Section: Biological Factors That Could Cause Biasmentioning
confidence: 99%
“…20 Moreover, changes in lifestyle, such as a decrease in the frequency of smoking and a decline in the penalties of sexually transmitted diseases and the growing availability of effective ART such as in vitro fertilisation (IVF) and intracytoplasmic sperm injection may have changed population fecundity in a favourable direction. 21,22 In contrast, the postponement of parenthood to ages when not only women but also men become less fertile, 23,24 and the growing epidemic of obesity 25 must have had a negative impact on population fecundity. It is impossible to assess the impact of each of these trends separately.…”
Section: Reproduction Fecundity and Fertility: What Is Their Relatiomentioning
confidence: 99%